A new evaluation method for overall heat transfer performance of supercritical carbon dioxide in a printed circuit heat exchanger. (1st August 2019) - Li, Xiong-hui; Deng, Tian-rui; Ma, Ting; Ke, Han-bing; Wang, Qiu-wang
Highlights: The large specific heat region benefits the heat transfer of supercritical fluid. The working point is proposed to evaluate the overall heat transfer performance. The validation of this method is performed in a double pipe heat exchanger. The heat transfer coefficient is higher when the working point is closer to 1. Abstract: Printed circuit heat exchangers are considered as one of the most promising candidates for the supercritical carbon dioxide Brayton cycle due to its high pressure resistance and high compactness. It is a critical component to exchange the heat between the primary loop and the secondary loop, which directly relates to the overall efficiency of the Brayton cycle. This work investigates the effect of supercritical carbon dioxide side inlet temperature and pressure on the overall heat transfer performance of a printed circuit heat exchanger with zigzag fins. A new evaluation method with working point is proposed to estimate the overall heat transfer performance, which considers the effects of working temperature and pressure. The results show that the overall heat transfer coefficient increases with the increase of mass flow rate and operating pressure, but performs the opposite changes with the increase of inlet temperature. A printed circuit heat exchanger will get better performance when the working point is closer to 1. This evaluation method is further validated under different operating conditions with available data from the open literature. The results show that the overall heat transfer coefficient peaks when the working point is closer to 1 for a double pipe heat exchanger.